PENGEMBANGAN MONOGRAF MATERI JAMUR (FUNGI) BERBASIS BIOENTREPRENEUR UNTUK MEMBERDAYAKAN MINAT BERWIRAUSAHA - Seprida Amiyati; Muhfahroyin Muhfahroyin; Agus Sutanto (LPPM UM Metro, 2020)
Learning in the 21st Century illustrates that students are able to solve problems with the environment. Whereas in entrepreneurship-based learning can be integrated through learning tools and can foster interest in student entrepreneurship. Learning needs analysis conducted by researchers at Minhajuttullab High School in Way Jepara sub-district, East Lampung, showed a lack of giving. Mushroom material and difficult to understand. The purpose of this development was to produce monographs as an interesting learning resource for monograph product students which contained entrepreneurship mushrooms that are easily understood by students and society in general. This type of research is Research and Development (R & D). This research was carried out in the High School Minhajuttullab Way Jepara in class X IPA. This R & D procedure was adapted from Sugiono which consisted of five steps, namely: 1) literature study and relevant research results, 2) designing and carrying out preliminary research, 3) developing / conceptualizing the model, 4) testing the model through experiments, 5) revisions model. Conclusion; 1) The mushroom moonograph Bioenterpener produced has been validated by user and expert learning, instrument validation, model validation, and is suitable for use.